Structural analysis, reactivity descriptors (HOMO-LUMO, ELF, NBO), effect of polar (DMSO, EtOH, H2O) solvation, and libido-enhancing potential of resveratrol by molecular docking - Eze A. Adindu; Obinna C. Godfrey; Eyuwa I. Agwupuye; Bassey O. Ekpong; Daniel C. Agurokpon; Sopuruchukwu E. Ogbodo; Innocent Benjamin; Hitler Louis (Chemical Physics Impact, 2023)
The profound impact of health challenges related to libido, encompassing sexual dysfunction, hormonal imbalances, relationship difficulties, stress, anxiety, depression, and the effects of certain medical conditions or medications, calls for urgent mitigative measures. As a result, this study meticulously explores the compound Resveratrol (Res) to uncover its substantial properties concerning libido enhancement. The compound was optimized using the DFT/ωB97XD/6–311G++(d, p) basis set in different solvents, namely DMSO (dimethyl sulfoxide), ethanol, and water. Notably, the geometry investigation reveals that the structural bond variations can be attributed to factors such as solvent polarity, screening effects, hydrogen bonding, solvation energy, and conformational preferences. Substantially, the Frontier Molecular Orbital (FMO) analysis explored the HOMO values of the compound in different solvents, resulting in 7.59198 eV, 7.5514 eV, and 7.59687 eV for RES_DMSO, RES_EtOH, and RES_H2O, respectively. Correspondingly, their LUMO values were found to be 7.5955 eV, 7.5648 eV, and 7.5982 eV, leading to respective band gaps of 0.0035 eV, 0.0133 eV, and 0.0014eV Remarkably, RES_H2O displayed the smallest energy gap (0.0014 eV) among the interacting compounds, indicating increased conductivity and sensitivity. Furthermore, the natural bond orbital analysis revealed that RES_H2O had the highest permutation energy among the three complexes (376.5 kcal/mol for RES_DMSO, 371.79 kcal/mol for RES_EtOH, and 378.77 kcal/mol for RES_H2O), indicating a stronger interaction between the donor and acceptor orbitals. Finally, the molecular docking studies unveiled a notable difference in binding affinity, with RES exhibiting a greater affinity for 1UDT at -8.1 kcal/mol compared to 1UDU, which demonstrated a binding affinity of -6.6 kcal/mol. Thus, RES has the potential to reverse erectile dysfunction and improve libido by inhibiting the activities of phosphodiesterase (1UDT and 1UDU), ultimately promoting vasodilatory signals from cGMP to the smooth muscles of the penis, leading to enhanced erection. These groundbreaking findings offer promising prospects for the development of new and effective drugs to combat various medical conditions.